MicroRNA-302d promotes the proliferation of human pluripotent stem cell-derived cardiomyocytes by inhibiting LATS2 in the Hippo pathway. (2nd July 2019) - Xu, Fei; Yang, Jingcheng; Shang, Jun; Lan, Feng; Li, Miaomiao; Shi, Leming; Shen, Li; Wang, Yongming; Ge, Junbo
Abstract : Recent evidence has shown that cardiomyocytes (CMs) can proliferate at a low level after myocardial infarction (MI), but it is insufficient to reestablish heart function. Several microRNAs (miRNAs) have been proven to sufficiently induce rodent CM proliferation. However, whether miRNAs identified in rodents can promote human CM proliferation is unknown due to the poorly conserved functions of miRNAs among species. In the present study, we demonstrate that i) expression of microRNA-302d (miR-302d) decreased significantly during CM differentiation from human pluripotent stem cells (hPSCs) from day 4 to day 18; ii) miR-302d efficiently promoted proliferation of hPSC-derived CMs; iii) miR-302d promoted CM proliferation by targeting LATS2 in the Hippo pathway; and iv) RNA-sequencing analysis revealed that overexpression of miR-302d induced changes in gene expression, which mainly converged on the cell cycle. Our study provides further evidence for the therapeutic potential of miR-302d.